2020
DOI: 10.3390/rel11010050
|View full text |Cite
|
Sign up to set email alerts
|

Non-Affiliated Believers and Atheists in the Very Secular Uruguay

Abstract: In recent years, literature in the field of religion has presented attempts to understand and characterize people who define themselves as believers but are not affiliated with any religious institution, along with those who define themselves as non-believers, or “nones”. Several quantitative studies covering this phenomenon in Latin America show clear disparities between the countries of the region. This article draws on a qualitative investigation into the way in which individuals relate to the transcendenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Desde esta perspectiva, el individuo debe liberarse de las imposiciones de una instituci ón religiosa (la Iglesia, en el caso latinoamericano), ya que esto opacaría su subjetividad (Roeland 2009, 46-47). Este elogio de la autenticidad, la libertad y la autonomía individuales, cuyos orígenes encontramos ya desde el siglo XVIII (Beck 2009), se ha difundido cada vez más en la población latinoamericana (Carozzi 1999;Da Costa 2020;Parker 2016;Rabbia et al 2019). En Colombia, este fenómeno se observa principalmente en sectores de las clases media y alta con capital cultural elevado (Sarrazin 2017), aunque no se descarta que también pueda observarse en sectores de estratos socioeconómicos bajos, tal como ocurre en otros países latinoamericanos (Parker 2016, 24).…”
Section: Discusi óNunclassified
“…Desde esta perspectiva, el individuo debe liberarse de las imposiciones de una instituci ón religiosa (la Iglesia, en el caso latinoamericano), ya que esto opacaría su subjetividad (Roeland 2009, 46-47). Este elogio de la autenticidad, la libertad y la autonomía individuales, cuyos orígenes encontramos ya desde el siglo XVIII (Beck 2009), se ha difundido cada vez más en la población latinoamericana (Carozzi 1999;Da Costa 2020;Parker 2016;Rabbia et al 2019). En Colombia, este fenómeno se observa principalmente en sectores de las clases media y alta con capital cultural elevado (Sarrazin 2017), aunque no se descarta que también pueda observarse en sectores de estratos socioeconómicos bajos, tal como ocurre en otros países latinoamericanos (Parker 2016, 24).…”
Section: Discusi óNunclassified
“…This showed that labeling the positive lifestyle change to atheism, rather than a secular one, resulted in negative perceptions and emotions because of the stereotypes attached to the term "atheism" (Brown-Iannuzzi et al, 2018;Gervais et al, 2011). Although atheism and secularism are not exact synonyms of one another, they both refer to being nonreligious (Cimino & Smith, 2007;Costa, 2020). An increasing number of countries are adopting a more secular society, however, a study done by Gervais et al (2017) found that despite a rise in secularism in countries around the world, there still exists a consistent antiatheist prejudice, where people viewed extreme moral violations as representative of atheists.…”
Section: Conversion/lifestyle Change and The Parole Boardmentioning
confidence: 99%